Linking PM10 and PM2.5 Pollution Concentration through Tree Coverage in Urban Areas (2023)
Particulate matter, PM10 and PM2.5, represents common air pollutants in cities and constitute a considerable threat to public health impacting daily activity of people living in city. In large cities, the main sources of PM10 and PM2.5 are diesel engine exhaust, brake dust, and particulate matter from vehicle tires. These particles can be deposited, filtered, and considerably reduced if there is a vegetative surface in the neighborhoods, thus eliminating a part of these particles and reducing their harmful footprint. This study evaluates the effect of tree coverage in urban areas on PM10 and PM2.5 removal considering air quality monitoring stations. Estimation of tree coverage is made by using high spatial and temporal resolution satellite images from Planet constellations. An empirical relationship between these two variables, with an acceptable correlation (R2 = 0.478 and R2 = 0.589 for PM10 and PM2.5, respectively), is obtained. A higher abundance of green space is associated with significantly lower PM10 and PM2.5 values. Preliminary results suggest that the amount of tree coverage do cause some degree of air quality improvement and can be used to inform national clean air strategies aimed at reducing pollutant emissions.